Laparoscopic-Assisted Vesicocalicostomy for Severe Pelvi-Ureteral Stricture Disease - Diaz, Edward C. (Society of Laparoendoscopic Surgeons, 2012)
A 39-year-old female previously treated with shock wave lithotripsy developed extensive ureteral stricture disease. After 2 unsuccessful attempts at retrograde balloon dilatation, she was evaluated at our center for further management. Successful reconstruction was performed with laparoscopic-assisted vesicocalicostomy.